EXPERIENCE OF BARRIERS TO HYPERTENSION MANAGEMENT IN MINANGKABAU ETHNIC GROUP IN PAYAKUMBUH INDONESIA: A PHENOMENOLOGICAL STUDY - Vera Kurnia; Dewi Suza; Yesi Ariani (Belitung Raya Foundation, Indonesia, 2018)
Background: Understanding barriers to hypertension managements remains important to reduce the hypertension rate in community. Minangkabau is one of the ethnic groups in West Sumatra Indonesia that has a high proportion of people with hypertension although its management has been implemented. Objective: This study aims to explore the experiences of barriers to hypertension management in Minangkabau ethnic group in Payakumbuh, Indonesia. Methods: This was a phenomenological study with twelve respondents selected using purposive sampling. Data were collected using in-depth interview. Colaizzi’s content analysis method was used for data analysis. Results: Five themes were emerged from the data, namely: (i) lack of self-motivation in the management of hypertension, (ii) disobedience in the management of hypertension, (iii) culture pattern of food intake, (iv) lack of social support, and (v) excessive stress and anxiety. Conclusions: The barriers to hypertension management in Minangkabau ethnic group are closely related to its culture both in lifestyle and in food intake of the family members and the community. Nurses are expected to always give health education about hypertension and finding the way to control it.